L??pis na m??o ou rolar no ch??o? olhares sobre a escolariza????o precoce e a corporeidade na educa????o infantil - Oliveira, Thiago Valim (2017)
This work aims to analyze the imbricated relationship between early schooling and corporality in Early Childhood Education. Early schooling, here, is seen as a pedagogical process that anticipates forms of teaching and learning typical of later stages, centralizing educational action in cognitive aspects to the detriment of other dimensions of development, such as corporeal. The corporeity, in turn, is crucial for the integral constitution of the subjects and is related to and influences the other factors of human formation (psychic, emotional and intellectual). The central question that governs the research is: What is the relation between early schooling and corporeality in Early Childhood Education? Thus, the general objective is to discuss the relationship between early schooling and bodywork in Early Childhood Education, approaching theorists that deal with this theme (s), and investigating how this relationship is effective in educational practice. Moreover, the present research is based on the hypothesis that the interviewed and observed teachers attend early school and thus minimize their bodily experiences in favor of more mechanical and repetitive activities, and this occurs, among other things, because of the pressure of the parents/responsible, the teachers of the later years and the school management. To do so, the research is carried out in a public school, in order to ascertain, in practice, how these teachers understand and practice this phenomenon. In order to base the theoretical reference, authors of critical pedagogy and developmental psychology were approached. The methodological option was based on a qualitative approach, making use of Content Analysis (CA) for the interpretation and treatment of the data obtained. It was concluded that the panorama to favors the early schooling over detriment of corporeity is a historical process originated from the attempt to legitimize the educational character of Early Childhood Education, and can thus lead to learning problems such as "Cognitive Acceleration". Another conclusion is that the interviewed and observed teachers don??t early educate the children and value their corporeity, since they have a diversified routine to follow and a conscious management of the peculiarities of the educational attendance to childhood. It should be emphasized that the initial conjecture did not materialize, since the locus was changed throughout the research.